TABOO WORDS IN STEPHEN KING’S NOVEL THE SHINING - Sembiring, M. Indra Arikami; Purwarno, Purwarno; Hariati, Puji (Universitas Islam Sumatera Utara, 2024)
This study investigates the use of taboo words by characters in Stephen King’s novel The Shining through a sociolinguistic approach, focusing on their types and functions. The novel follows Jack Torrance, his wife Wendy, and their son Danny, whose stay at the Overlook Hotel leads Jack into a spiral of psychological instability and violence. This research categorizes and quantifies the types and functions of taboo words, applying a descriptive qualitative method complemented by quantitative analysis. The primary data source was the novel itself, with the researcher as the primary instrument and a data sheet as a secondary tool. Results indicate four types of taboo words: epithets, profanity, obscenities, and vulgarities, totaling 300 instances. Profanity appears most frequently (123 instances, 41%), with obscenities following at 79 instances (26.33%). Epithets account for 63 instances (21%), while vulgarities occur least often at 35 instances (11.67%). Further, analysis of the functions of taboo words reveals that characters use them in auxiliary (126 instances, 42%), expletive (101 instances, 33.67%), abusive (63 instances, 21%), and humorous (10 instances, 3.33%) capacities. The dominance of the auxiliary function suggests that characters frequently incorporate taboo language into regular speech patterns rather than using it for direct insult. The minimal presence of the humorous function aligns with the novel's intense psychological horror and supernatural atmosphere, which limits comedic expression.